Pengembangan Aplikasi Rancaka Berbasis Literasi Digital untuk Pembelajaran Aksara Jawa dan Sandhangan Siswa Kelas IV Sekolah Dasar - Asrinda Riska Cahyawati; Endang Sri Maruti; Sesaria Prima Yudhaningtyas (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to develop and test the feasibility of the RANCAKA (National Learning Space for Love of Javanese Script) application based on digital literacy as a learning medium for Javanese script and sandhangan for fourth-grade elementary school students. The background of the study is based on the problem that Javanese language learning is still dominated by conventional methods, the media used are not varied, and students’ understanding and interest in Javanese script and sandhangan are low. This study uses the Research and Development (R&D) method with the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The trial subjects were fourth-grade students of SDN 02 Madiun Lor. Data were collected through observation, interviews, and validation questionnaires, and analyzed descriptively and quantitatively. The results show that the RANCAKA application meets the feasibility criteria with material expert validation percentage of 92% (Very Feasible), language expert 81.82% (Very Feasible), and media experts 78% (worthy), with an overall average of 83.94% (very worthy). Student responses to the use of the application were also very positive, namely 93.3% in individual tests, 90% in small group tests, and 88% in field trials. Based on these results, it is concluded that the RANCAKA application based on digital literacy is feasible, practical, and effective to use as a learning medium for Javanese script and sandhangan, and can support the development of digital literacy skills for elementary school students.